"Certified … now what?" On the Challenges of Lifelong Learning: Report from an AMEE 2017 Symposium. Issue 1 (1st January 2018) - Sehlbach, Carolin; Balzan, Martin; Bennett, Jonathan; Prior Filipe, Helena; Thinggaard, Ebbe; Smeenk, Frank
ABSTRACT: The increasing mobility of patients and healthcare professionals across the countries of Europe has highlighted the wide variations in both medical training, and provision of medical competency and skills. The maintenance of the standards defining competency and skills have national and international implications and have proved challenging for national regulatory bodies. Thus each nation has introduced different types of Continuing Professional Development (CPD), recertification and relicensing systems. At the Symposium entitled: " 'Certified … now what?' On the Challenges of Lifelong Learning" in August 2017 at the Association for Medical Education in Europe (AMEE) annual conference, we reviewed differing European national relicensing systems were reviewed. The review highlighted various lifelong learning and competence assessment approaches using examples from different medical specialties across several European countries.